Perancangan Sistem Pengendalian Suhu pada Gedung Bertingkat dengan Teknologi Wireless Sensor Network - Sugiarto, Bambang (Jurnal Energi Dan Manufaktur; Vol 4, No.1 April 2010, 2012)
At the building, for example the office building, hotels or the apartment, is needed by a controlsystem of the temperature. This is caused the number of rooms so it is difficult to monitor the use ofAir Conditioning (AC) for each room. This control system is used to monitor the temperature ofeach room so as to be able to control the use of AC. This paper will discuss the designing of controltemperature by using technology of Wireless Sensor Network (WSN). WSN technology made use ofthe Zigbee wireless network as the data communication, where each room was installed by atemperature sensor (the node sensor). The node sensor that is installed in each room are connectedwith each other and make the star, the tree or mesh network formation. The advantages of thissystem is using Zigbee wireless that is free of the licence. The results of the temperaturemonitoring of each node sensor are afterwards gathered in the Base Stasion Controller (BSC) thatbecame the centre of managing and processing the data, so as to be formed a control system of thetemperature of each room to this building.
Keywords: temperature, wireless sensor network, zigbee